Human-Centered Design and Iterative Refinement of Tools and Methods to Implement a Surveillance and Risk Prediction System for Clinical Deterioration in Ambulatory Cancer Care - Daniel J. France; Paromita Nath; Jason Slagle; Shilo Anders; Megan Salwei; Timothy Vogus; Hannah Slater; Carrie Reale; Laurie Novak; Lori-Anne Parker-Danley; Zachary Kohutek; Rajiv Agarwal; et al. (ACI Open, 2025)
Background A common cause of preventable harm is the failure to detect and appropriately respond to clinical deterioration. Timely intervention is needed, particularly in medically complex patients, to mitigate the effects of adverse events, disease progression, and medical error. This challenging problem requires clinical surveillance, early recognition, timely notification of the appropriate clinicians, and effective intervention.